Panda a panda - Kocmanová, Michaela (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Předmětem diplomové práce bylo zpracování projektové dokumentace pro provádění stavby. Objekt má splňovat podmínky dané pro budovy s téměř nulovou spotřebou energie. Navrhovaným objektem se stal pavilon pro pandy velké s restaurací, který je situován do Zoologické zahrady hl. m. Prahy na parcelu s číslem 1491/1. Novostavba je navržena jako částečně podsklepený objekt s jedním podzemním a dvěma nadzemními podlaží. Objekt je zastřešen jednoplášťovou plochou vegetační střechou. Z hlediska provozního se v navrženém pavilonu nachází dva rozdílné provozy. Prvním provozem je chov pand velkých. Druhým provozem je pak restaurace. K objektu přiléhají dva venkovní výběhy, které jsou s vnitřní expozicí propojeny pomocí spojovacích ramp. Výhled do výběhů je návštěvníkům umožněn ze střešní terasy nad 1. nadzemním podlažím. Objekt pavilonu pro pandy velké je částečně monolitická a částečně zděná stavba s kontaktním zateplovacím systémem. Svislé i vodorovné nosné konstrukce jsou v 1. PP a 1. NP monolitické železobetonové. 2. NP je zděné z pórobetonových tvárnic. Stropní konstrukce nad 2.NP je skládaná z předpjatých stropních panelů. Objekt je zastřešen jednoplášťovou plochou vegetační střechou.

This diploma thesis presents a project documentation for construction of a zoo pavilion with a restaurant. The structure has to be designed in compliance with regulations for buildings with almost zero energy consumption. Its construction site is located within the existing compound of Prague’s zoo on plot no. 1491/1. The pavilion is proposed to house giant pandas. The building has three floors- one underground and two above. It is covered by a flat green roof. In terms of circulation, the structure is composed from two parts. The first one is formed by premises for the pandas, including necessary facilities for their wellbeing and their breeding; and the second part is visitors’ part, including restaurant, gift shop and amenities. The building is enclosed by two exterior expositions for pandas which are connected with the interior exposition premises by two ramps- tunnels. There is a roof terrace adjacent to the restaurant for visitors to enjoy the view of pandas in their exterior grounds. The vertical structure of the pavilion for giant pandas is a combination of load bearing brick walls and cast-in-place concrete walls- the underground floor and the ground floor is formed by the cast-in-place concrete walls and the upper floor is formed by the brick walls made out of autoclaved aerated concrete blocks. The horizontal structures are formed by prestressed concreted floor panels or in the case of the upper floor by cast-in-place reinforced concrete slabs.
Panda & panda
Keywords: Pavilon pro pandy velké; zoologická zahrada; restaurace; vegetační střecha; provětrávaná fasáda; Pavilion for giant pandas; zoological garden; restaurant; green roof; ventilated facade